Inovasi dalam Pendidikan : Pembelajaran dari Finlandia untuk Transformasi Pendidikan di Indonesia - Ahmad Zainiansyah; Muhammad Abel Afif; Mislaini Mislaini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Finland's education system has been recognized globally as one of the best in the world, primarily because of the innovation it implements. This article explores various aspects of educational innovation in Finland, such as flexible curricula, student-based learning approaches, teacher autonomy, and a focus on student welfare, as well as their relevance to educational transformation in Indonesia. By comparing the two countries' education systems, this research identifies the main challenges facing Indonesia, including disparities in education quality, reliance on standardized tests, and disparities in access to education. Through critical analysis, this article proposes the application of Finnish innovation principles, such as simplifying the curriculum, strengthening teacher training, and implementing formative assessment, which are adapted to the Indonesian socio-cultural context. In addition, this article highlights the importance of equal access to educational resources to support the sustainability of reform. These findings provide strategic insight for policy makers, educators and other stakeholders in improving the quality and inclusiveness of the Indonesian education system.